2014
DOI: 10.4319/lo.2014.59.3.0645
|View full text |Cite
|
Sign up to set email alerts
|

Diversity trumps acidification: Lack of evidence for carbon dioxide enhancement of Trichodesmium community nitrogen or carbon fixation at Station ALOHA

Abstract: We conducted 11 independent short-term carbon dioxide (CO 2 ) manipulation experiments using colonies of the filamentous cyanobacteria Trichodesmium isolated on three cruises in the North Pacific Subtropical Gyre (NPSG). Dinitrogen (N 2 ) and carbon (C) fixation rates of these colonies were compared over CO 2 conditions ranging from , 18 Pa (equivalent to last glacial maximum atmospheric P CO2 ) to , 160 Pa (predicted for , year 2200). Our results indicate that elevated P CO2 has no consistent significant effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 54 publications
5
39
0
Order By: Relevance
“…On the other hand, Ren et al (2009Ren et al ( , 2012 interpret δ 15 N records from the western tropical North Atlantic and Pacific as reduced N 2 fixation, in response to lower N-loss in the glacial ocean. Some specific N 2 -fixing Trichodesmium species may also be limited by CO 2 concentrations of surface waters (Barcelos e Ramos et al, 2007;Hutchins et al, 2007), which could have reduced N 2 fixation during the LGM, although other studies investigating Trichodesmium community assemblages (Gradoville et al, 2014) and unicellular diazotrophs (Law et al, 2012) found no consistent effect of CO 2 on N 2 fixation.…”
Section: Introductionmentioning
confidence: 89%
“…On the other hand, Ren et al (2009Ren et al ( , 2012 interpret δ 15 N records from the western tropical North Atlantic and Pacific as reduced N 2 fixation, in response to lower N-loss in the glacial ocean. Some specific N 2 -fixing Trichodesmium species may also be limited by CO 2 concentrations of surface waters (Barcelos e Ramos et al, 2007;Hutchins et al, 2007), which could have reduced N 2 fixation during the LGM, although other studies investigating Trichodesmium community assemblages (Gradoville et al, 2014) and unicellular diazotrophs (Law et al, 2012) found no consistent effect of CO 2 on N 2 fixation.…”
Section: Introductionmentioning
confidence: 89%
“…However, experiments including several different diazotrophic strains suggest that the response to increased pCO 2 is strain-specific and depends on the CO 2 uptake kinetics of each diazotroph type (Hutchins et al, 2013). Similarly, field studies have found divergent responses to increasing pCO 2 levels, indicating that different phylotypes are unequally affected by acidification, which results in a diluted effect on bulk N 2 fixation field measurements (e.g., Gradoville et al, 2014). Heterotrophic N 2 fixation in hypoxic zones (Hamersley et al, 2011), suggests that the predicted expansion of OMZs (Stramma et al, 2008b) will likely enhance global N 2 fixation rates too, either by in situ heterotrophic N 2 fixation, or by the enhancement of diazotrophy in other oceanic areas in order to balance increased denitrification occurring in the OMZs (Deutsch et al, 2007).…”
Section: What Is There Left To Be Known?mentioning
confidence: 99%
“…There is low to medium confidence on the effects of ocean acidification on nitrogen (N 2 ) fixing cyanobacteria. A wide range of N 2 fixation responses under RCP8.5 conditions have been observed in laboratory experiments Eichner et al, 2014;Gradoville et al, 2014), possibly due to speciesspecific differences in the mechanisms of N 2 fixation (Eichner et al, 2014).…”
Section: Updates To Ar5mentioning
confidence: 99%